2018
DOI: 10.1152/jn.00116.2018
|View full text |Cite
|
Sign up to set email alerts
|

The cross education of strength and skill following unilateral strength training in the upper and lower limbs

Abstract: We examined cross education of strength and skill following 6 wk of unilateral training and 6 wk of detraining. A novel finding was the continued increase in contralateral strength following both training and detraining. Neuromuscular adaptations were highly correlated with strength gains in the trained and contralateral limbs. Motor learning was evident in the trained and contralateral limbs during contractions performed without concurrent feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 65 publications
(92 reference statements)
2
32
2
Order By: Relevance
“…Training of one limb through task repetition improves the performance with the contralateral, untrained limb [9][10][11][12] , a phenomenon known as cross transfer. For instance, increased peak acceleration was observed in both left and right hands performing index finger abduction after the unilateral training of the finger abduction of the right hand 10,13 .…”
mentioning
confidence: 99%
“…Training of one limb through task repetition improves the performance with the contralateral, untrained limb [9][10][11][12] , a phenomenon known as cross transfer. For instance, increased peak acceleration was observed in both left and right hands performing index finger abduction after the unilateral training of the finger abduction of the right hand 10,13 .…”
mentioning
confidence: 99%
“…Researchers believe that a hallmark of expertise is the ability to sustain high velocities while demonstrating greater than average or excellent improvements in accuracy (Englehorn, 1997). While we are uncertain of why this ratio improved, previous research in strength literature has shown a decrease in force variation that transferred from contralateral training to the untrained limb (Green et al 2018A). Future research will need to investigate if this underlies the changes we see in this study.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, extensive research has been done in strength training using very controlled unilateral movements. However, the improvement of motor skills is an important clinical aspect that has been widely overlooked in contralateral training literature (Green et al, 2018A). Recent research (Green et al, 2018B) has demonstrated that training in the contralateral arm reduced variability of force in the ipsilateral arm indicating an increase in skill.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training can counter decrease in muscle strength, and increase in muscle strength has been documented through resistance training with ≥60% of maximal muscle strength (10). Indeed, the finding that unilateral training increases muscle strength mainly in the trained lateral limb, but not in the contralateral untrained limb (14), substantiates the effects induced by training on muscles. Unilateral training of both lateral limbs increases unilateral muscle strength but not bilateral strength, whereas bilateral training increases bilateral muscle strength but not the unilateral strength (9,24,32); this phenomenon is known as lateral specificity in resistance training (32).…”
mentioning
confidence: 58%